LO49: Characterizing highly frequent users of a large Canadian urban emergency department. (15th May 2017) - Kim, J.; Kwok, E.S.; Cook, O.; Calder, L.
Abstract : Introduction: Highly frequent users (HFU) of the emergency department (ED) remain a poorly defined and complex population. This study describes patient and visit characteristics for HFU of the ED, and analyzes subgroups of patients with mental illness, substance abuse, and/or ≥30 yearly ED visits.Methods: We performed a health records review of 250 randomly selected adults with >99 th percentile of ED visit frequency (≥7 visits) at a tertiary care academic hospital with two EDs in 2014. Two reviewers collected demographic variables (age, sex, and comorbidities) and visit data (ED diagnosis, ED length of stay (LOS), ED presentation time (daytime 0800-1559 h, evening 1600-2359 h, overnight 2400-0759 h), consultation services, and final disposition). Data were analyzed using descriptive and univariate analyses, student t and Mann Whitney U tests.Results: Of 897 eligible patients who experienced 9, 376 ED visits we included 250 patients (2, 670 visits) in our main analyses, and an additional 11 patients (494 visits) outside of the random selection with ≥30 ED visits. Mean age was 53.4±1.3 (SEM), and 55.6% were female. Most patients had a fixed address (88.9%), and a family physician (87.2%). Top comorbidities included gastrointestinal (61.6%), cardiovascular (52%), and chronic pain issues (47.2%). Top ED diagnoses included musculoskeletal pain (9.6%), abdominal pain (8.4%) and alcohol-related presentations (8.5%). Hospital admission was required for 15.6% of visits. From all possible visits (3164 visits), consultations for social workers, geriatric emergency medicine nurses, or Community Care Access Centres were made for 5.9% of visits, with 47.3% of these patients presenting during daytime hours. Among visits requiring these consultations, median ED LOS was greatest in the evening (12.7 hours, range 1.4-45.2 hours), compared to daytime (5.4, 1.2-33.6; p=0.0002) or overnight (7.9, 1.0-38.3, p=0.02). Inter-rater review of 4.5% of abstracted health records revealed a kappa score of 0.8.Conclusion: This study highlights that a remarkably low proportion of HFUs received allied health consultations at the study sites, likely corresponding to a lack of available consultants outside of daytime work hours. Our findings suggest the need to address significant gaps in order to balance the clinical needs of patients who frequent the ED with currently available resources.